A high efficient node capture attack algorithm in wireless sensor network based on route minimum key set. Issue 2 (19th June 2012) - Wu, Guowei; Chen, Xiaojie; Obaidat, Mohammad S.; ,; Lin, Chi
ABSTRACT Wireless sensor networks are often deployed in hostile and unattended environment that are very prone to node capture attack. In node capture attack, information such as key, data on captured nodes, can all be extracted by the adversary. Node capture attack in wireless sensor networks suffers from low efficiency and high resource expenditure. To enhance the efficiency of node capture attack, we propose here a high efficiency node capture attack algorithm that is based on route minimum key set, namely greedy node captured based on route minimum key set (GNRMK). To obtain the route minimum key set, the sensor network is mapped as a flow network. The route minimum key set can be calculated by the maximum flow of the flow network. Then, an overlapping value is assigned to each node on the basis of route minimum key set. The node with maximum overlapping value will be captured in every round of attack. Simulation results indicate that, compared with other node capture attack schemes, GNRMK can compromise the network by capturing fewer nodes. Moreover, the fraction of traffic compromised is much higher. Copyright © 2012 John Wiley & Sons, Ltd.